2009
DOI: 10.3171/2009.2.focus0926
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and radiobiology of brain arteriovenous malformations: implications for risk stratification in natural history and posttreatment course

Abstract: Brain arteriovenous malformations (BAVMs) are an important cause of intracerebral hemorrhage (ICH) in young adults. Biological predictors of future ICH risk are lacking, and controversy exists over previous studies of natural history risk among predominantly ruptured BAVM cohorts. Recent studies have suggested that the majority of BAVMs are now diagnosed as unruptured lesions, and that the risk according to natural history among these lesions may be less than previously assumed. In the first part of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 101 publications
2
21
0
1
Order By: Relevance
“…17 Embolization may induce hypoxia, which makes the tissue less radiosensitive and increases the angiogenic activity of the BAVM, 18,19 rendering it an active instead of a static lesion. 20,21 Moreover, it has been shown that hypoxia-inductible factor and vascular endothelial growth factor are expressed more frequently in embolized than in nonembolized BAVMs 18 in surgical specimens. …”
Section: Discussionmentioning
confidence: 99%
“…17 Embolization may induce hypoxia, which makes the tissue less radiosensitive and increases the angiogenic activity of the BAVM, 18,19 rendering it an active instead of a static lesion. 20,21 Moreover, it has been shown that hypoxia-inductible factor and vascular endothelial growth factor are expressed more frequently in embolized than in nonembolized BAVMs 18 in surgical specimens. …”
Section: Discussionmentioning
confidence: 99%
“…3 The prevalence of AVMs is estimated at 1.1 per 100,000 with autopsy cases excluded or 2.1 per 100,000 for all cases. The Cooperative Study of Intracranial Aneurysms and SAH reported a prevalence of 140-500 per 100,000.…”
Section: Arteriovenous Malformationsmentioning
confidence: 99%
“…3,22,40 Cerebral AVMs have a reported annual spontaneous hemorrhage rate of 1%-4%, with potentially devastating consequences at the time of rupture. 3,13,21,40 As such, current consensus guidelines recommend screening patients with possible or definite HHT for cerebral vascular malformations (CVMs) using MRI with and without contrast enhancement, including sequences to detect blood products to increase sensitivity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,29 Large high-grade AVMs are often located in or near eloquent areas, such as the motor cortex. Surgery can be destructive as a result of direct damage to the brain, especially during severe intraoperative hemorrhage, or as a result of ischemia caused by obstruction of arteries, which have en passant feeders combined with a large or essential cerebral perfusion territory.…”
mentioning
confidence: 99%